Discriminative grandparental investment – the impact of grandchild’s gender and sociodemographic parameters - Kirchengast, Sylvia; Putz, Beatrix (Anthropological Review, 2016)
Homo sapiens is a typical cooperative breeder and grandparents are among the most important caregivers besides the mothers. Grandparental investment however differs markedly between maternal and paternal grandparents but also between grandmothers and grandfathers. From an evolutionary viewpoint this differential grandparental investment is mainly explained as a result of paternity uncertainty. On the other hand emotional support and child care help from grandparents may also be associated with sociocultural factors. The present study focused on the impact of grandchild’s gender, but also grandparental age and occupation on discriminative grandparental investment, i.e. solicitude, contact frequency and quality of relationship. 272 adults persons between the age 18 and 35 years (x= 23.5yrs; ±3.7) were enrolled in the study. Patterns of grandparental investment during childhood as well as quality of the grandparent- grandchild relationship were collected retrospectively using a 57 item questionnaire. As to be expected maternal grandmothers showed the highest contact frequency and the highest solicitude while -as to be expected - the paternal grandfather exhibited the lowest degree of investment. Grandparental investment was independent of grandparent category mainly influenced by residential distance. Grandchild’s gender and sociodemographic characteristics of the grandparents in contrast had a minor impact on grandparental caregiving and contact frequency. Contrary, grandchild’s gender was related significantly with the quality of relationship and emotional closeness.